2022
DOI: 10.3390/ijerph192113898
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Per- and Polyfluoroalkyl Substances (PFAS) and Cardiometabolic Biomarkers in Adults of Czechia: The Kardiovize Study

Abstract: Even though there is evidence of decreasing trends of per- and polyfluoroalkyl substances (PFAS) in Czechia, there are still major sources of PFAS pollution. Regarding the still-inconsistent results of the relationship between cardiometabolic health and PFAS, the present study sought to determine the association between PFAS levels and the presence of cardiometabolic biomarkers, including blood pressure and dysglycemia drivers in the Czech population. A cross-sectional study with 479 subjects (56.4% women, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Some studies report that the body burden of some PFAS is associated with higher body mass index, larger waist circumference, and higher fat mass. [47][48][49] Three studies have reported negative associations between PFAS body burden and body size characteristics. 47,50,51 Moreover, several studies have reported no associations between PFAS body burden and body size.…”
Section: Obesitymentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies report that the body burden of some PFAS is associated with higher body mass index, larger waist circumference, and higher fat mass. [47][48][49] Three studies have reported negative associations between PFAS body burden and body size characteristics. 47,50,51 Moreover, several studies have reported no associations between PFAS body burden and body size.…”
Section: Obesitymentioning
confidence: 99%
“…[47][48][49] Three studies have reported negative associations between PFAS body burden and body size characteristics. 47,50,51 Moreover, several studies have reported no associations between PFAS body burden and body size. [52][53][54][55][56] To date, epidemiological studies do not support consistent associations between PFAS and obesity.…”
Section: Obesitymentioning
confidence: 99%
See 3 more Smart Citations